Preparation and characterization of clean, single-crystalline YHx films (0≤x≤2.9) on W(110) - Hayoz, J.; Pillo, T.; Bovet, M.; Guthrie, St.; Pastore, G.; Schlapbach, Louis; Aebi, Philipp (My University, 2000)
Yttrium can be loaded with hydrogen up to high concentrations causing dramatic structural and electronic changes of the host lattice. We report on the preparation of clean, single-crystalline YHx films (0≤x≤2.9). The films have been characterized in situ combining angle-resolved photoelectron spectroscopy (ARPES) and low energy electron diffraction. Direct Y dihydride growth, i.e., Y evaporation under a H2 partial pressures of ≈5×10–6 mbar at 500 K on W(110), is the most convenient starting point for the preparation of clean single-crystalline Y hydride films covering H concentrations from the "clean metal" (x≈0) up to the lower boundary of the pure trihydride phase (x≈2.9). Upon annealing Y dihydride films the desired H concentration can be adjusted within the α-phase or the (α+β) two-phase regime. On the other hand, the extension of our photoelectron spectrometer with an homemade ultrahigh vacuum (UHV) compatible hydrogenation system allows to induce the transition from Y dihydride to Y trihydride within a few minutes. The hydrogenation system combines a high-pressure reaction cell with hydrogen permeation through a Pd–24%Ag tube. The overall design is such that the sample never gets in contact with non-UHV compartments. For direct Y dihydride growth on W(110) two equally populated face-centered- cubic(111) domains rotated by 180° with respect to each other are observed. In the α- and γ-phase the Y atoms form a hexagonal-close-packed(0001) oriented lattice. Furthermore, the previously established model for in situ H concentration estimation in Y [J. Hayoz et al., Phys. Rev. B 58, R4270 (1998)] is extended successfully from the α to β to the to γ-phase transition. Ultraviolet photoemission spectroscopy data unequivocally reveal the opening of a gap extending as far as 1 eV below EF for normal electron emission upon the phase-transformation from Y dihydride to Y trihydride. It also appears that the H absorption rate strongly depends on the H2 purity. Our experimental results demonstrate the capability of this setup for in situ preparation and investigations on the geometrical and electronic structure of Y hydride films and, more generally, rare-earth hydride films using ARPES.